Weak acid leaching of MgB2 to purify magnesiothermic boron powder. (March 2021) - Capra, Marco; Bovone, Gianmarco; Loria, Federico; Bernini, Cristina; Hopkins, Simon C.; Ballarino, Amalia; Tropeano, Matteo; Tumino, Andrea; Grasso, Gianni; Ferdeghini, Carlo; Putti, Marina; Vignolo, Maurizio
Abstract: We have established a new procedure for recovering boron contained in oxidized MgB2 phase. Incorrect conditions of synthesis or conservation, or excess impurities in precursors, can lead to MgO formation with consequent degradation of superconducting properties, thus representing a possible problem in the industrial production of MgB2 conductors following the ex-situ PIT process. A procedure has been developed in order to dissolve MgO (due to the oxidization of Mg in MgB2 phase) and to decompose the MgB2 phase into elemental B and a soluble Mg salt. The process can also be successfully applied to low-grade B in order to enhance the purity, providing that the B is first reacted into MgB2 . In fact, MgB2 synthesis converts residual B2 O3 (present in B) and other impurities to leachable compounds. For the present work, an ill-preserved MgB2 powder produced in 2008 was treated with glacial acetic acid. The reduction of impurities and secondary phases was monitored along each step of the proposed process by X-ray diffraction (XRD) technique and by energy dispersion spectroscopy (EDS) analysis. The purification process was successfully applied on two different MgB2 powders: the first was synthesized using commercial B (H. C. Starck), the second using a different magnesiothermic B with a low purity grade prepared by freeze-drying process at CNR-SPIN. An interesting result is that, after acidic treatment of MgB2, the resulting B particles are finer and more amorphous than pristine B particles. The increased surface area of B undoubtedly offers a more reactivity of powders versus the weak acid, because the impurities within the B particles are exposed to the direct action of the acid and not longer protected by B crust.